Diagnostic and prognostic significance of long noncoding RNA LINC00173 in patients with melanoma - Wang,Mujun (2022)
SUMMARY OBJECTIVE: A growing volume of literature has suggested long noncoding RNAs (lncRNAs) as important players in tumor progression. In this study, we aimed to investigate the expression and prognostic value of lncRNA LINC00173 (LINC00173) in melanoma. METHODS: LINC00173 expression was measured in 163 paired cancerous and noncancerous specimen samples by real-time polymerase chain reaction. The correlations between LINC00173 expression with clinicopathological characteristics and prognosis were analyzed by chi-square test, log-rank test, and multivariate survival analysis. Receiver-operating characteristic curves were used for the assessment of the diagnostic value of LINC00173 for melanoma patients. RESULTS: The expression level of LINC00173 in melanoma specimens was distinctly higher than that in adjacent non-neoplasm specimens (p<0.01). Besides, LINC00173 was expressed more frequently in patients with advanced melanoma than in patients with early melanoma. Multivariate assays confirmed that LINC00173 expression level was an independent prognostic predictor of melanoma patients (p<0.05). CONCLUSION: Our data indicated that LINC00173 expression could serve as an unfavorable prognostic biomarker for melanoma patients.